Analisis Harga Diri, Efikasi Diri, dan Lokus Kendali pada Pokdarwis Putra Lon Malang - Faisol, Achmad; Irawati, S. Anugrahini (Management Department of Economics and Business Of Trunojoyo Madura University, 2023)
This study aimed to find out the description of Self Esteem, Self Efficacy, and Locus of Control at Pokdarwis (tourism awareness group) Putra Lon Malang, the organization that manages Lon Malang Beach. This research was a qualitative study with descriptive approach. The determination of informants was carried out using a purposive sampling technique and the data collection procedures employed observations, interviews, and documentation. Data analysis techniques used data reduction, data presentation, and conclusion. In addition. To ensure the validity of the data, the researcher employed credibility, transferability, dependability, and confirmability tests through triangulation (combination). The results showed that the organization managing the Lon Malang Beach tourist attraction, in this case, the Pokdarwis Putra Lon Malang, had a high level of self esteem, they are aware of the power or ability to control visitor activities to direct, reprimand, and even give strict punishment to visitors who break the rules with confidence. Regarding the self-efficacy of the Pokdarwis Putra Lon Malang members, they are confident in their ability to complete every task that is their responsibility as the organization that manages the tourist attraction. Regarding locus of control, they tend to believe that everything that happens in life is under self-control.